Pulmonary aspergilloma presenting with recurrent hemoptysis in a patient with previously treated pulmonary tuberculosis: a case report from a rural hospital in Ketapang Regency - Herick Alvenus Willim; Eva Lydia Munthe; Widi Mujono (Indonesian Vascular Access Association (IVAA), 2023)
Introduction: Pulmonary aspergilloma, also known as mycetoma or fungus ball, is a type of pulmonary aspergillosis characterized by colonizing fungi within a preexisting lung cavity, typically in previously healed tuberculosis (TB). We present a case report from a rural hospital in Ketapang Regency, Indonesia, highlighting the complexities of diagnosing and managing pulmonary aspergilloma in a patient with a history of treated pulmonary TB. Case Description: A 32-year-old man with recurrent hemoptysis, fever, weight loss, and productive cough sought care after years of inconclusive tests. Despite a history of pulmonary TB and multiple negative acid-fast bacilli tests, a thorax computed tomography scan showed the presence of aspergilloma within the upper lobe of the left lung. He was given antifungal therapy. During follow-up, he continued to experience recurrent hemoptysis. Eventually, he was referred to a provincial referral hospital with cardiothoracic surgical facilities for definitive surgical management. Conclusion: Pulmonary aspergilloma presents significant challenges in diagnosis and management. Recurrent or massive hemoptysis, a hallmark symptom of this condition, demands vigilant attention in patients with a history of pulmonary TB.